Treatment of experimental pneumocystosis: review of 7 years of experience and development of a new system for classifying antimicrobial drugs. - Walzer, P D (1992)
Over a 7-year period, we analyzed 261 dose regimens of antimicrobial drugs in the treatment and prevention of Pneumocystis carinii pneumonia in an immunosuppressed rat model. These compounds ranged from drugs in clinical use to newly synthesized agents. Drug efficacy was expressed as the magnitude of the reduction in median P. carinii cyst or nucleus counts on a scale ranging from inactive (less than 5-fold) to very markedly active (greater than or equal to 1,000-fold). The classification system was reproducible and allowed drugs studied at different times to be compared with each other. The system demonstrated a hierarchy of anti-P. carinii activity not only among classes of compounds but also among individual members of a drug class. Sulfonamides, sulfones, and diamidines were the most active agents; some purine nucleosides and nitrofurans also showed promising activity; and most antiparasitic, antifungal, antibacterial, and antiviral drugs were inactive. We conclude that this classification system represents a simple, quantitative method of comparing the activities of antimicrobial drugs against P. carinii. Information gained from this system should be helpful in developing new anti-P. carinii compounds and establishing standard procedures for their evaluation.